2012
DOI: 10.1158/1535-7163.mct-12-0041
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Inhibition Alters Anaplastic Thyroid Carcinoma Tumor Metabolism and Improves Response to Conventional Chemotherapy and Radiation

Abstract: Anaplastic thyroid carcinoma (ATC) accounts for over 50% of thyroid cancer mortality and is generally refractory to conventional treatment. Based on recent studies, we hypothesized that ATC metabolism can be targeted to improve response to chemo-radiotherapy. Eight established and authenticated ATC cell lines were sequenced at 140 sites contained within 26 commonly mutated genes to identify novel potential therapeutic targets. Cellular proliferation, energy and reducing potential stores were measured under con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 27 publications
2
82
0
Order By: Relevance
“…Tumor metabolism was challenged using 2DG (31) (N=9), external radiation therapy (32) (N=7), or conditional gene expression (19) (N=3); controls were tested prior to or without perturbation (N=33) or administered a negative control (N=3). All three kinetic models fit these datasets (N=55) reasonably well, as summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor metabolism was challenged using 2DG (31) (N=9), external radiation therapy (32) (N=7), or conditional gene expression (19) (N=3); controls were tested prior to or without perturbation (N=33) or administered a negative control (N=3). All three kinetic models fit these datasets (N=55) reasonably well, as summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is reasonable to assume that the increased ROS levels induced by oxamate synergistically enhanced the DNA damage effect and toxicity of irradiation in NPC cells. Other studies also found that glycolysis inhibitors increased radiosensitivity in cancer cells (33)(34)(35). Sharma et al (34) reported that non-coordinated expression of antioxidant enzymes was another essential factor that led to selective radiosensitization in malignant cells, in addition to redox status.…”
Section: Discussionmentioning
confidence: 96%
“…HNSCC cell lines containing TP53 constructs have been previously described by our group and were obtained for the experiments detailed here within the last 4 months. (6, 7)…”
Section: Methodsmentioning
confidence: 99%